Study of the statistical properties of the detected cosmic rays - I. Angelov; B. Vachev; V. M. Vashchenko; A. M. Lytvynenko; E. Malamova; V. M. Pavlovych; V. D. Rusov; J. Stamenov (Ядерна фізика та енергетика)
The results of statistic analysis of Cherenkov radiation detection data are presented. Some abnormalities in Fourier and wavelet spectra of the analyzed process have been found.